1996
DOI: 10.1002/ana.410390312
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram syndrome: Hereditary diabetes mellitus with brainstem and optic atrophy

Abstract: Wolfram syndrome was originally described as a combination of familial juvenile-onset diabetes mellitus and optic atrophy. Other neurological features subsequently emerged, and "DIDMOAD" (diabetes insipidus, diabetes mellitus, optic atrophy, and deafness) became a commonly accepted acronym. Here, we describe 4 further cases from 2 families, in whom there occurred previously unrecognized neurological features, central apnea and neurogenic upper airway collapse, together precipitating primary respiratory failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 35 publications
1
54
0
2
Order By: Relevance
“…[137][138][139][140][141][142][143][144] Most cases have been classified as sporadic or recessively inherited. The hallmark of all these cases is the association of juvenile diabetes mellitus and progressive visual loss with optic atrophy, almost always associated with diabetes insipidus, neurosensory hearing loss, or both (hence, the eponym DIDMOAD for diabetes insipidus, diabetes mellitus, optic atrophy, and deafness).…”
Section: Other Monosymptomatic Hereditary Optic Neuropathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[137][138][139][140][141][142][143][144] Most cases have been classified as sporadic or recessively inherited. The hallmark of all these cases is the association of juvenile diabetes mellitus and progressive visual loss with optic atrophy, almost always associated with diabetes insipidus, neurosensory hearing loss, or both (hence, the eponym DIDMOAD for diabetes insipidus, diabetes mellitus, optic atrophy, and deafness).…”
Section: Other Monosymptomatic Hereditary Optic Neuropathiesmentioning
confidence: 99%
“…138,139 Other systemic and neurologic abnormalities include ataxia, axial rigidity, seizures, startle myoclonus, tremor, gastrointestinal dysmotility, vestibular malfunction, central apnea, neurogenic upper airway collapse, ptosis, cataracts, pigmentary retinopathy, iritis, lacrimal hyposecretion, tonic pupil, ophthalmoplegia, convergence insufficiency, vertical gaze palsy, mental retardation, psychiatric abnormalities, nystagmus, short stature, primary gonadal atrophy, other endocrine abnormalities, anosmia, megaloblastic and sideroblastic anaemia, abnormal electroretinography, and elevated cerebrospinal fluid protein. 137,139,140,[143][144][145] Psychiatric disorders are also seen at an increased frequency among heterozygous carriers. 146 Pathology and neuroimaging in some patients reveal widespread atrophic changes and suggest a diffuse neurodegenerative disorder, with particular involvement of the midbrain and pons.…”
Section: Other Monosymptomatic Hereditary Optic Neuropathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these diagnostic syndromes, most WS patients have highly variable clinical symptoms including several neurological abnormalities such as nystagmus, mental retardation, and seizures (1). Moreover, several studies have shown diffuse and widespread atrophy in the brain (19,22). Central respiratory failure due to brainstem atrophy has described as a common cause of death, indicating the significance of neurodegeneration in WS (1,22).…”
mentioning
confidence: 99%
“…Os achados ao exame de ressonância magnética do cérebro são ausência de sinal de alta intensidade da neuro-hipófise, atrofia da região hipotalâmica, cerebelo, tronco e córtex cerebral, além de atrofia do nervo e quiasma óptico (17,(25)(26)(27). Dados de autópsia mostram uma perda de neurônios com distrofia e edema axonal, freqüentemente associados com gliose e áreas de desmielinização sem sinais de inflamação (28,29).…”
Section: Complicações Do Sncunclassified